Fundamentals of nuclear reactor physics study aid - Kuznetsov, M. S. physicist Associate Professor of Tomsk Polytechnic University, Candidate of Technical Sciences 1984- (TPU Publishing House, 2023)
Training book contains information about basic neutron and physical processes of power atomic reactors. The main attention is paid to issues of neutrons interactions with different materials and components of reactors installations as well as neutrons cycle including multiplication, termolization and diffusion. The examples of solving practical problems are given in this textbook. The book is intended for students studying in the directions 14.03.02, 14.04.02 "Nuclear physics and technologies", 14.05.02 "Nuclear power plants: design, operation and engineering", 14.05.04 "Electronics and automation of physics installations".